Biodiesel Synthesis with Different Feedstock Oils: Free Fatty Acid Analysis and Fuel Properties Characterization - Hamid, Abdul; Badrus Syafa', Muhammad; Esti Purbaningtias, Tri; Rahmawati, Zeni; Fatah, Misbakhul; Wahyuni, Tri; Dayi Febriana, Ike; Abdullah , Mohammad; Rohmah, Faizatur (Universitas Islam Indonesia, 2026)
The present study evaluates the feasibility of non-edible and waste oils as sustainable feedstocks for biodiesel production through a two-step esterification–transesterification process. Waste cooking oil, Calophyllum inophyllum oil, and sunflower oil were employed as raw materials, with sodium hydroxide used as the base catalyst during transesterification. The initial free fatty acid content varied significantly among the feedstocks, ranging from 29.38% in Calophyllum inophyllum oil to 3.20% in waste cooking oil and 1.28% in sunflower oil. Acid-catalyzed esterification effectively reduced the free fatty acid levels, enabling efficient conversion during the subsequent transesterification step. Fourier transform infrared spectroscopy confirmed the successful formation of fatty acid methyl esters, indicated by the presence of characteristic ester functional group absorption bands. Methyl oleate is the dominant component in all biodiesel samples, reaching 83.12% in sunflower oil biodiesel. The produced biodiesel exhibited kinematic viscosities of 4.61-5.63 cSt and flash points of 164-175 °C, meeting ASTM D6751 specifications.